Competitive Advantages of Joint Stock Commercial Bank for Investment and Development of Viet Nam in Retail Banking Market = Lợi thế cạnh tranh của Ngân hàng TMCP đầu tư và phát triển Việt Nam trên thị trường Ngân hàng bán lẻ. Luận văn ThS. Kinh - Hà, Thanh Lương (2019)
CHAPTER 1: THEORETICAL FRAMEWORK ON COMPETITIVE ADVANTAGES OF COMMERCIAL BANKS IN THE RETAIL BANKING MARKET. CHAPTER 2: REALITY OF COMPETITIVE ADVANTAGES OF BIDV. CHAPTER 3: SOLUTIONS FOR BUILDING COMPETITIVE ADVANTAGES OF BIDV IN THE RETAIL MARKET.